THE EFFECT OF TIKTOK EDUCATION FOR INCREASING THE READING ABILITY OF EIGHTH GRADE STUDENTS AT SMP 18 IN BENGKULU CITY - Gilang Halen Meyrandha; Ferri Susanto; Syamsul Rizal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The integration of social media into education continues to evolve, with TikTok emerging as a potential learning medium. This study aims to investigate the effect of using TikTok educational content on improving the reading ability of eighth-grade students at SMP Negeri 18 Bengkulu. The research applied a quasi-experimental design with a non-equivalent control group model. A total of 52 students were divided into two groups: the experimental group received instruction through TikTok-based content, while the control group received conventional teaching. The reading test, administered as both pre-test and post-test, was used as the research instrument and analyzed using an Independent Sample t-test with SPSS version 25.0. The results showed a significant difference between the two groups, with a p-value of 0.043 (< 0.05), indicating that the use of TikTok has a positive impact on students’ reading comprehension. Therefore, TikTok can be considered an effective alternative medium for English language learning, especially in enhancing students' reading skills.